OPTIMASI AMOBILISASI ENZIM XILANASE DARI Trichodema viride MENGGUNAKAN MATRIKS KITOSAN-TRIPOLIFOSFAT - Sutrisno, Sutrisno; Suratmo, Suratmo; Sa'idah, Ilmiyati (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
Xylanase is an enzyme that has an ability to hydrolyze hemicellulose and has an important act in such as industries, so that should be immobilized so that it can be used repeatedly and easy to removed from the product. In this study, xylanase isolated from the fungus Trichoderma viride and purified by using ammonium sulfate saturation levels 40-80%. The method that used in the immobilization of xylanase is a method of trapping using a matrix of chitosan-tripolyphosphate with make a variation to chitosan concentration (0.5, 1.0, 1.5, 2.0, 2.5)% (w / v) and make a variation to enzyme concentration (0.5, 1.5, 2.5, 3.5, 4.5) mg / mL. The results showed that the chitosan concentration optimum is at a concentration  2.0% with the amount of xylanase stuck at  such as 3.867 mg. Enzyme concentration optimum is at a concentration of 4.5 mg / mL with the amount of xylanase stuck such as 18.942 mg.